Morphology and Anatomy Characteristic of Pisang Awak (Musa paradisiaca cv. Awak) in West Kalimantan - Ari Sunandar; Adi Pasah Kahar (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Indonesia is the origin and center of diversity of banana. One of an edible banana in Indonesia is Pisang Awak (Musa paradisiaca cv. Awak ). In West Kalimantan, the ripe Pisang Awak has been processed into sale (dried banana). The aims of this research were to describe the morphological and anatomical character of Pisang Awak in West Kalimantan, Indonesia. In this study, Pisang Awak were collected from Padang Tikar I village, Batu Ampar Sub-district, Kubu Raya district, West Kalimantan. Morphological characterizations were conducted by following the instruction on Descriptors for Banana (Musa spp.) from IPGRI. The root, leaf blade, and petiole were fixed in FAA solution. Root, leaf, and petiole anatomy preparats were made by paraffin method. The lamina of Pisang Awak consisted of adaxial epidermis, two hypodermis layers, two palisade layers, spongy layer, bundle sheath cell, abaxial epidermis, laticifer. The petiole of Pisang Awak composed of three tissue systems, i.e., epidermis layer, parenchyma tissue and vascular tissue. The root of Pisang Awak consists of two epidermis layers, parenchyma and vascular cylinder. In the future, morphological and anatomical character in Pisang Awak could be applied as the basis of information for breeding programs of banana cultivars and classification.